Some New Generating Functions for the Modified Laguerre Polynomials (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we obtain some new results on bilateral generating functions of the modified Laguerre polynomials. We also get generating function relations between the modified Laguerre polynomials and the generalized Lauricella functions. Some special cases and important applications are also discussed.